Fluid shear stress triggers cholesterol biosynthesis and uptake in inner medullary collecting duct cells, independently of nephrocystin-1 and nephrocystin-4 - Garfa Traoré, Meriem; Roccio, Federica; Miceli, Caterina; Ferri, Giulia; Parisot, Mélanie; Cagnard, Nicolas; Lhomme, Marie; Dupont, Nicolas; Benmerah, Alexandre; Saunier, Sophie; Delous, Marion (Frontiers in Molecular Biosciences, 2023)
Renal epithelial cells are subjected to fluid shear stress of urine flow. Several cellular structures act as mechanosensors–the primary cilium, microvilli and cell adhesion complexes–that directly relay signals to the cytoskeleton to regulate various processes including cell differentiation and renal cell functions. Nephronophthisis (NPH) is an autosomal recessive tubulointerstitial nephropathy leading to end-stage kidney failure before adulthood. NPHP1 and NPHP4 are the major genes which code for proteins that form a complex at the transition zone of the primary cilium, a crucial region required for the maintenance of the ciliary composition integrity. These two proteins also interact with signaling components and proteins associated with the actin cytoskeleton at cell junctions. Due to their specific subcellular localization, we wondered whether NPHP1 and NPHP4 could ensure mechanosensory functions. Using a microfluidic set up, we showed that murine inner medullary collecting ductal cells invalidated for Nphp1 or Nphp4 are more responsive to immediate shear exposure with a fast calcium influx, and upon a prolonged shear condition, an inability to properly regulate cilium length and actin cytoskeleton remodeling. Following a transcriptomic study highlighting shear stress-induced gene expression changes, we showed that prolonged shear triggers both cholesterol biosynthesis pathway and uptake, processes that do not seem to involve neither NPHP1 nor NPHP4. To conclude, our study allowed us to determine a moderate role of NPHP1 and NPHP4 in flow sensation, and to highlight a new signaling pathway induced by shear stress, the cholesterol biosynthesis and uptake pathways, which would allow cells to cope with mechanical stress by strengthening their plasma membrane through the supply of cholesterol.